Correlation between cusp pattern and deflecting wrinkle in six ethnic groups from southwestern Colombia - Parra-Correa, Lina María; Hernández-Silva, Jesús Alberto; Moreno-Correa, Sandra; Moreno-Gómez, Freddy (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: the cusp pattern and the deflecting wrinkle are two morphological traits whose expression and variability contribute to the morphological configuration of the occlusal surface of deciduous and permanent lower molar teeth. The objective of the present study was to estimate the correlation between cusp pattern and deflecting wrinkle in six ethnic groups from southwestern Colombia. Methods: analysis of 480 plaster models corresponding to 100 mixed Caucasoid mestizos from Cali (50 men and 50 women), 60 Afro-descendants from Cali (34 women and 26 men), 84 Afro-descendants from Puerto Tejada (42 women and 42 men), 116 Afro-descendants from Villa Rica (57 men and 59 women), 60 misak indigenous (37 women and 23 men) and 60 nasa indigenous (35 women and 25 men). Results: there were high frequencies (over 60%) of cusp pattern (Y expression) and deflecting wrinkle (grades 2 and 3) in deciduous first lower molars, mid frequencies (between 40 and 59%) of cusp pattern (Y and + expressions) and deflecting wrinkle (grades 1 and 2) in permanent first lower molars, and mid frequencies (between 40 and 59%) of cusp pattern (+ and X expressions) and deflecting wrinkle (grades 1 and 2) in permanent lower second molars. Conclusions: these frequencies suggest a trend in cusp pattern, which may vary according to the degree of expression of the deflecting wrinkle. This tendency consists of the Y cusp pattern when the deflecting wrinkle is expressed in grades 2 and 3. Bilaterally was observed and there was no sexual dimorphism.